Elegy for a Prairie Town - H. C. Palmer (Symphony in the Flint Hills, 2014)
A poem by H.C. Palmer on lost prairie towns and how nature slowly reclaims them.
Keywords: poem; poetry; Kansas; poet; town; ghost; prairie; Bushong Piano